Bioinformatics for the synthetic biology of natural products: integrating across the Design–Build–Test cycle. Issue 8 (17th May 2016) - Carbonell, Pablo; Currin, Andrew; Jervis, Adrian J.; Rattray, Nicholas J. W.; Swainston, Neil; Yan, Cunyu; Takano, Eriko; Breitling, Rainer
Abstract : Bioinformatics tools facilitate and accelerate all steps along the Design–Build–Test cycle of synthetic biology, for the enhanced production of natural products in engineered microbes. Abstract : Covering: 2000 to 2016 Progress in synthetic biology is enabled by powerful bioinformatics tools allowing the integration of the design, build and test stages of the biological engineering cycle. In this review we illustrate how this integration can be achieved, with a particular focus on natural products discovery and production. Bioinformatics tools for the DESIGN and BUILD stages include tools for the selection, synthesis, assembly and optimization of parts (enzymes and regulatory elements), devices (pathways) and systems (chassis). TEST tools include those for screening, identification and quantification of metabolites for rapid prototyping. The main advantages and limitations of these tools as well as their interoperability capabilities are highlighted.